Does Apoptosis Regulate the Function of Retinal Photoreceptors? - Halaby, Reginald (Medical Hypothesis, Discovery & Innovation Ophthalmology, 2012)
Apoptosis, or programmed cell death, is an integral component of developmental biology, embryology, and anatomy. All eukaryotic cells possess the molecular machinery necessary to execute apoptosis. However, dysregulated apoptosis in the form of too much or too little cell death results in diseases such as Alzheimer’s disease, autoimmune disorders, and cancer. It is postulated that apoptosis of the photoreceptors in the retina plays a vital role in mediating vision, and evidence is presented here to support this hypothesis. However, the precise mechanisms that regulate this cell death in photoreceptors have yet to be fully elucidated.